Crystal structure of 5′-hydroxy-6′-methoxy-1′-methyl-2′,3′,8′,8a′-tetrahydro-1′H-spiro[cyclohexane-1,7′-cyclopenta[ij]isoquinoline]-2,5-dien-4-one, C18H19NO3 - Yang Li-Qiong; Wu Jie; Qin Hai-Long; Cai Pan-Feng; Liu Ya-Hua; Li Ji-Xin (Zeitschrift für Kristallographie - New Crystal Structures)
C18H19NO3, monoclinic, P21 (no. 4), a = 10.0669(6) Å, b = 6.9690(4) Å, c = 11.9051(7) Å, β = 113.011(2)°, V = 768.76(8) Å3, Z = 2, Rgt(F) = 0.0344, wRref(F2) = 0.0849, T = 170 K.